The bloodless boy - Lloyd, Robert J. (Hooke and Hunt mysteries ; book 1, 2021)
"The City of London, New Year's Day, 1678. Eleven years have passed since the Great Fire ripped through the City. Twenty since the death of Cromwell and the restoration of a king. London is gripped by hysteria, where rumours of Catholic plots and sinister foreign assassins abound. When the body of a young boy drained of his blood is discovered on the snowy bank of the Fleet River, Robert Hooke, the Curator of Experiments of the Royal Society for the Improving of Natural Knowledge, and his assistant Harry Hunt, are called in to explain such a ghastly finding -- and whether it's part of a plot against the king. Wary of the political hornet's nest they are walking into -- and using scientific evidence rather than paranoia in their pursuit of truth -- Hooke and Hunt must discover why the boy was murdered, why his blood was taken. And what does the strange sequence of numbers inscribed on his body mean?" --